Filarial infection modulates the immune response to Mycobacterium tuberculosis through expansion of CD4+ IL-4 memory T cells - Chatterjee, Soumya (J Immunol, 2015)
Exaggerated CD4+T helper 2-specific cytokine producing memory T cell responses developing concomitantly with a T helper1 response might have a detrimental role in immunity to infection caused by Mycobacterium tuberculosis (Mtb). To assess the dynamics of antigen (Ag)-specific memory T cell compartments in the context of filarial infection we used multiparameter flow cytometry on PBMCs from 25 microfilaremic filarial -infected (Inf) and 14 filarial-uninfected (Uninf) subjects following stimulation with filarial (BmA) or with the Mycobacterium tuberculosis (Mtb)-specific Ag CFP10. Our data demonstrated that the Inf group not only had a marked increase in BmA-specific CD4+IL-4+ cells (Median net frequency compared to baseline (Fo)=0.09% vs. 0.01%, p=0.038) but also to CFP10 (Fo =0.16% vs. 0.007%, p=0.04) and Staphylococcal Enterotoxin B (SEB) (Fo =0.49% vs. 0.26%, p=0.04). The Inf subjects showed a BmA-specific expansion of CD4+CD45RO+IL-4+ producing central memory (T(CM), CD45RO+CCR7+CD27+) (Fo =1.1% vs. 0.5%, p=0.04) as well as effector memory (TEM CD45RO+CCR7-CD27-) (Fo =1.5% vs. 0.2%, p=0.03) with a similar but non-significant response to CFP10. In addition, there was expansion of CD4+ IL-4+ CD45RA+ CCR7+CD27+ (naïve-like) in Inf individuals compared to Uninf subjects. Among Inf subjects with definitive latent tuberculosis , there were no differences in frequencies of IL-4 producing cells within any of the memory compartments compared to the Uninf group. Our data suggest that filarial infection induces antigen-specific, exaggerated IL-4 responses in distinct T cell memory compartments to Mtb-specific antigens, which are attenuated in subjects who are able to mount a delayed type hypersensitivity reaction to Mtb.